Effects of alumina on the thermal processing of apatite-wollastonite: Changes in sintering, microstructure and crystallinity of compressed pellets. Issue 15 (December 2020) - Melo, Priscila; Kotlarz, Marcin; Marshall, Martyn; Magallanes, Marlin; Ferreira, Ana Marina; Gentile, Piergiorgio; Dalgarno, Kenneth
Abstract: In this work we investigated the sintering behaviour of apatite-wollastonite (AW) glass-ceramic powders with the presence of alumina, firstly detected as a potentially useful surface contaminant derived from the ball milling of the powder, and then as a dopant in the glass formulation. All powders were benchmarked against AW without alumina. A small percentage of contamination (0.14 wt%) showed to delay the melting of material, and lower densification derived from a lower ability to crystallize and higher stability in the glassy states. The doped AW revealed that an increase in alumina favoured the formation of a glassy phase, increasing the degree of necking and the development of crystals. In conclusion, the introduction of alumina improves the AW glass-ceramic processability when content and process parameters are optimized.